1979
DOI: 10.1002/1097-0142(197907)44:1<131::aid-cncr2820440123>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Receptor sites for complement and for immune complexes on human nonhemopoietic tumor cells

Abstract: Tumor cells in primary cultures derived from 11 untreated nonhemopoietic cancer patients were reacted with specifically coated sheep erythrocytes. Rosette formation between tumor and indicator cells was assessed, Eight of the primary cultures reacted positively with both IgG-coated (EAIgG) and with IgM-human complement coated (EAIgMC or EAIgMC 4,3) sheep erythrocytes. EAIgG rosette formation in positive cultures ranged from 25 to 85%, and for EAIgMC/EAIgMC 4,3 reactivity ranged between 22--95%. Rosette formati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1981
1981
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…At the same time, Isaac Witz showed the presence of IgG within non-lymphoid tumor tissue and observed that these IgG did not exhibit any antibody activity against tumor antigens, suggesting that they bound to tumor cells via their Fc region [50]. This hypothesis was supported by further experiments where primary cultures of tumors and SRBC formed rosettes [51, 52]. In addition, it was observed that tumor cells injected in mice immunized with non-tumoral antigens were able to bind antibody via their Fc region [53].…”
Section: Expression Of Tumor Fcγriibmentioning
confidence: 98%
“…At the same time, Isaac Witz showed the presence of IgG within non-lymphoid tumor tissue and observed that these IgG did not exhibit any antibody activity against tumor antigens, suggesting that they bound to tumor cells via their Fc region [50]. This hypothesis was supported by further experiments where primary cultures of tumors and SRBC formed rosettes [51, 52]. In addition, it was observed that tumor cells injected in mice immunized with non-tumoral antigens were able to bind antibody via their Fc region [53].…”
Section: Expression Of Tumor Fcγriibmentioning
confidence: 98%
“…Some previous reports have established that most Fe receptor-bearing cells within tumours were macrophages (Kerbel & Pross, 1976, Wood & Gollahon, 1977 and the Fe receptor has thus been caused as an index of host infiltration into the tumours (Kerbel & Pross, 1976). Other authors have claimed the presence of Fe receptors on tumour cells also (T0nder et al, 1978;Biran et al, 1979) and on a large proportion of TIL (Hayry & T0tterman, 1978;Vose et al, 1977). In malignant melanoma, the largest population of infiltrating cells were esterase-negative, non-phagocytic, non-T and non-B cells with Fc receptors (Roubin et al, 1975).…”
Section: Discussionmentioning
confidence: 96%
“…At the same time, Witz et al showed the presence of IgG within non-lymphoid tumor tissue and that these IgG did not exhibit any antibody activity against tumor antigens suggesting that they bound to tumor cells likely via their Fc region [39]. This hypothesis was supported by further experiments where the formation of rosettes between cells from primary cultures of tumors and SRBC was observed [40,41]. In addition, it was observed that tumor cells injected in mice immunized with non-tumoral antigens were able to bind antibody via their Fc region [42].…”
Section: Ectopic Expression Of Fcγr On Non-hematopoietic Tumor Cellsmentioning
confidence: 91%